Dangers of the chronic stress response in the context of the microbiota-gut-immune-brain axis and mental health: a narrative review - Warren, Alison; Nyavor, Yvonne; Beguelin, Aaron; Frame, Leigh A. (Frontiers in Immunology, 2024)
13 More than 20% of American adults live with a mental disorder, many of whom are treatment 14 resistant or continue to experience symptoms. Other approaches are needed to improve mental health 15 care, including prevention. The role of the microbiome has emerged as a central tenet in mental and 16 physical health and their interconnectedness (well-being). Under normal conditions, a healthy 17 microbiome promotes homeostasis within the host by maintaining intestinal and brain barrier integrity, 18 thereby facilitating host well-being. Owing to the multidirectional crosstalk 19 between the microbiome and neuro-endocrine-immune systems, dysbiosis within the microbiome is a 20 main driver of immune-mediated systemic and neural inflammation that can promote disease 21 progression and is detrimental to well-being broadly and mental health in particular. In predisposed 22 individuals, immune 23 dysregulation can shift to autoimmunity, especially in the presence of physical or psychological 24 triggers. The chronic stress response involves the immune system, which is intimately involved with 25 the gut microbiome, particularly in the process of immune education. This interconnection forms the 26 microbiota-gut-immune-brain axis and promotes mental health or disorders. In this brief review, we 27 aim to highlight the relationships between stress, mental health, and the gut microbiome, along with 28 the ways in which dysbiosis and a dysregulated immune system can shift to an autoimmune response 29 with concomitant neuropsychological consequences in the context of the microbiota-gut-immune- 30 brain axis. Finally, we aim to review evidenced-based prevention strategies and potential therapeutic 31 targets.